Physical Properties of White Pepper as Affected by Skin-Peeling Method: A Comparative Study of Soaking and Boiling on Green and Red Pepper Fruits - Andi Muhammad Tegar Mengembara; Muhammad Tahir Sapsal; Junaedi Muhidong; Febriana Intan Permata Hati (Salaga Journal, 2026)
Skin-peeling method is a critical determinant of white pepper quality. This study evaluated the effects of two skin-peeling treatments, soaking at room temperature (30 °C for 10–14 days) and boiling at high temperature (100 °C for 10 minutes), on three physical properties of white pepper produced from green and red pepper fruits (Piper nigrum L.): moisture content (wet-basis/MC wb and dry basis/ MC db), color attributes (L*, a*, b*), and hardness. A total of 150 fresh pepper fruits from Bulukumba Regency, sorted at two maturity levels (green and red, 5.5–6.0 mm diameter), were divided into four treatment groups. This study was descriptive and comparative in nature without statistical replication; results are presented as single-point observations. The boiling treatment produced the lowest MC wb in peeled red pepper (LMPK: 8.83%), the only sample approaching the maximum threshold set by SNI 0004:2013 (≤13.0%). Soaking resulted in MC wb values of 25.05% for peeled pepper across both maturity levels. In terms of surface lightness, soaked peeled red pepper (LMRK: L* = 11.86) outperformed boiled peeled red pepper (LMPK: L* = 8.51), indicating that soaking better preserved kernel brightness. Hardness values of peeled pepper ranged from 27.68 N (LHPK) to 36.62 N (LMPK), with the boiling treatment producing comparable or slightly higher hardness than soaking. The soaking method produced brighter white pepper kernels, while boiling more effectively reduced moisture content and is better suited when shelf life is the priority.